On event studies and distributed-lags in two-way fixed effects models: Identification, equivalence, and generalization - Kurt Schmidheiny; Sebastian Siegloch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We discuss important properties and pitfalls of panel-data event study designs. We derive three main results. First, binning of effect window endpoints is a practical necessity and key for identification of dynamic treatment effects. Second, event study designs with binned endpoints and distributed-lag models are numerically identical leading to the same parameter estimates after correct reparametrization. Third, classic dummy variable event study designs can be generalized to models that account for multiple events of different sign and intensity of the treatment, which are particularly interesting for research in labor economics and public finance. We show the practical relevance of our methodological points in a replication study.
Keywords: C23; C51; H00; J08; 330; event study; distributed-lag; applied microeconomics; credibility revolution